Application for Building Permit on Lot 1, 2 Block 106 - Baptist Church::::::::: (1907)
The City Clerk is George W. Robbins. The Petitioner is Akin and Thurlow. The Contractor is Akin and Thurlow. The address is probably 1301 Osos.